Pengaruh Struktur Modal Terhadap Nilai Perusahaan dan Kinerja Perusahaan Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia - Rizky Mangondu; Yossi Diantimala (Jurnal Dinamika Akuntansi dan Bisnis, 2016)
This study is aimed at examining the effect of capital structure on firm value and firm performance. The population in this research is banking companies listed in Indonesia Stock Exchange for three years (2021-2014). Using purposive sampling method, a sample of 54 companies is obtained. The analytical method used in this research is the analysis of linear regression. The results of this research shows that capital structure have a negative effect on firm value and firm performance.